Analisis Kemampuan Pemecahan Masalah Matematis Ditinjau dari Self Confidence Siswa Kelas VIII - Zukhriya, Rohmatin; Kartono , Kartono; Wijayanti, Kristina (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2024)
Mathematical problem-solving ability is one of the basic skills that helps students solve mathematical problems. This study aims to describe mathematical problem-solving skills based on the level of self-confidence. The research method is descriptive and qualitative. In this study, testing instruments and questionnaires were used for data collection. The study participants were six students which students representing high, medium, and low self-confidence categories with the sampling technique using a purposive sampling technique. The data analysis techniques in this study are data reduction, data presentation, and conclusion. The study findings show that students in the high confidence category could meet all the indicators of mathematical problem-solving ability. Students in the medium confidence category can meet three indicators of mathematical problem-solving ability, namely, constructing new knowledge through problem-solving, implementing and adapting appropriate plans/strategies to solve problems, and solving problems that arise in mathematics and other situations. Meanwhile, students in the low confidence category can meet the indicator of the mathematical problem-solving ability to construct new knowledge through problem-solving. Therefore, this research is expected to provide input for teachers to design lessons that can help students develop their mathematical problem-solving skills.